THE PERFORMANCE OF EXPLICIT FORMULAS FOR DETERMINING THE DARCY-WEISBACH FRICTION FACTOR - Minhoni, Renata T. de A. [UNESP]; Pereira, Francisca F. S. [UNESP]; Silva, Tatiane B. G. da [UNESP]; Castro, Evanize R. [UNESP]; Saad, Joao C. C. [UNESP] (Soc Brasil Engenharia Agricola, 2020)
The Darcy-Weisbach equation is the most recommended equation for determining the pressure loss in pressurized pipes because of its wide applicability. However, one of the largest obstacles to implementing this equation is the friction factor (f) calculation. This factor can be precisely determined using the Colebrook equation, which is implicit. Thus, the objective of this study was to compare six explicit equations for calculating the Darcy-Weisbach friction factor with the implicit Colebrook equation based on the relative error. Based on the results, the equations of Vatankhah and Offor & Alabi were the most highly recommended. These six explicit formulas showed a mean relative error of less than 1% compared to the Colebrook equation, except for the Swamee and Jain equation, for which the laminar regime generated a mean relative error of 1.83%.
Keywords: absolute roughness; Colebrook equation; forced conduits; head loss; hydraulic load; Reynolds number